THE IMPACT OF AGROCHEMICALS AS THE ELEMENTS OF CULTIVATION TECHNOLOGIES OF PRODUCTIVE PEAS IN THE SOUTH OF THE ROSTOV REGION - S. A. Vasilchenko; G. V. Metlina; A. R. Ashiev; Yu. V. Laktionov (Зерновое хозяйство России)
For the Russian Federation, pea is a traditional cultivated agricultural crop, demanded both in the food industry for its excellent taste and in livestock for a high content of forage units and balanced protein (up to 90% of the protein are of easily soluble albumin and globulins), which contribute to lower costs for animal feeding. The current paper has presented the working results of the laboratory of row crop cultivation technology (FSBSI “Agricultural Research Center “Donskoy”) for 2015–2016, which studied the impact of growth stimulants (“Etikhol”, “Gumistim”), bioorganic fertilizers “Intermag Profi”, and biological product “Rizotorfin” on the productivity of the middle-ripening pea variety “Aksaysky usaty 7”. The soil of the experimental plot is favorable for peas growing, as the humus content in the arable layer is 3.36%, pH is 7.0, P2 O5 is 24.4; K2 O is 360 mg per one kg of soil. The studied preparations had an impact on the elements of the yield structure and grain productivity. Productivity has significantly improved due to application of most fertilizers. The largest productivity increase on 0.57 t/ha or 26.4% to the control was observed with the use of “Intermag Profi”. This experiment had also better energetic and economic indicators compared to other variants. The increase of net energy income compared to control was 9.48 GJ/ha, the decrease in energy intensity was on 1.14 GJ/t, the increase of energetic efficiency was on 0.59 units. The increase of net income was on 6507 rubles/ha, the cost of production reduced on 1232 rubles/ton and profitability increased on 27%.